Empowering ECAs in handheld devices - Goh, Ong Sing; Depickere, Arnold; Fung, Chun Che; Wong, Kok Wai (Japan Society for Fuzzy Theory and Intelligent Informatics, 2006)
The growth of mobile services on mobile phones or PDA has been significant in the recent years. This has opened up a new arena for many organizations to implement services on these mobile devices. In this paper, we propose an extension to our work in Artificial Life; of having our embodied conversational agents (ECAs) framework to be extended for mobile handheld devices. We present an overview and investigate new challenges on the implementation of the ECAs on the cross-platform architecture suitable for small end user devices. We demonstrated the proposed downsizing framework suitable for mobile devices with the application in the area of crisis communication.